Original paper Granuloma faciale – analysis of 5 cases - Michajłowski, Igor; Sobjanek, Michał; Kozicka, Dorota; Dobosz, Magdalena; Włodarkiewicz, Adam (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction : Granuloma faciale (GF) is an uncommon inflammatory dermatosis. The treatment of GF remains a challenge considering the unclear aetiopathogenesis. Various therapeutic methods have been described. Aim : To analyse the clinical picture and treatment results in a group of patients with GF. Material and methods : Five adults with GF were analysed and treated. Diagnosis was confirmed by histological examination. Patients were treated with surgery, cryosurgery, topically with corticosteroids and tacrolimus. The follow-up period varied from 5 to 15 months. Results : Complete resolution was observed in 3 cases, partial remission was noted in 1 case. In 1 case the treatment was unsuccessful. Conclusions : The treatment of GF remains a challenge. It is difficult to determine the most effective therapy. Topical tacrolimus and cryosurgery seem to be the first line treatment.